The Analgesic Efficacy of Kinesiology Taping in Delayed Onset Muscle Soreness (DOMS) - Grażyna Adler; Julia Kruszyniewicz; Karolina Skonieczna-Żydecka; Radosław Sroka (Central European Journal of Sport Sciences and Medicine, 2016)
Aims and scope: Delayed Onset Muscle Soreness (DOMS) develops after intense physical activity and its mechanisms are due to inflammation. Kinesiology Taping (KT) improves microcirculation, supports myofascial functions and relieves the tissue. The aim of this study was to verify whether KT has an analgesic action in the DOMS and whether somatotype is associated with this action. Materials and Methods: There were 20 healthy subjects aged 27.7 ±6.4 years with moderate or high physical activity included into the study. The training with emphasis on eccentric muscle work was performed. Somatotype of respondents was assessed by Heath-Carter method. While DOMS occurred, KT muscle application on one of the limbs was done. For the next five days subjects filled out questionnaires in which they served intensity of pain on the basis of Visual Analogue Scale (VAS). Results and conclusions: In the limb where KT application was used a significant (p < 0.05) reduction in the intensity of DOMS compared to the limb without application was observed. It was found that the somatotype has no effect on the reduction of DOMS (p > 0.05). Conclusions: KT exhibits analgesic properties in DOMS. Somatotype has no relation to the effectiveness of KT analgesic efficacy in DOMS.